2007
DOI: 10.3892/or.18.3.703
|View full text |Cite
|
Sign up to set email alerts
|

Detection of drug-resistance genes using single bronchoscopy biopsy specimens

Abstract: Expression of three major resistance genes MDR1, MRP1 and LRP was investigated in small cell lung cancer, non-small cell lung cancer and metastasis. Single biopsies of bronchoscopy from 73 patients were performed to investigate expression of these three resistance genes by reverse transcriptase-polymerase chain reaction. Relations between gene expression and patient age, smoking status, histology, and chemotherapy were evaluated. A more frequent expression of MDR1 (77 versus 66%), MRP1 (91 versus 72%) and LRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…In addition, some studies showed that over-expression of P-gp is associated with MDR in different types of cancer, leading to poor patient prognosis [46][47][48]. We also demonstrated that increased expression of P-gp in lung tumor tissues ( Figure 4) compared with adjacent non-tumor tissues, consistent with previous reports [49][50][51]. It is worth noting that some studies have correlated P-gp overexpression with negative survival outcomes, including treatment failure and relapse [52][53][54].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, some studies showed that over-expression of P-gp is associated with MDR in different types of cancer, leading to poor patient prognosis [46][47][48]. We also demonstrated that increased expression of P-gp in lung tumor tissues ( Figure 4) compared with adjacent non-tumor tissues, consistent with previous reports [49][50][51]. It is worth noting that some studies have correlated P-gp overexpression with negative survival outcomes, including treatment failure and relapse [52][53][54].…”
Section: Discussionsupporting
confidence: 90%
“…However, radiation in MDR cells has also been demonstrated to mediate loss of extrachromosomally amplified MDR1 genes, concomitant with a reduction in P-gp levels (25). Fractionated irradiation led to the restoration of drug sensitivity by the downregulation of P-gp in MDR cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…Biopsies from progressing cancer showed higher MDR1, MRP1 and LRP gene expression. These findings have revealed the high gene expression of MDR1 and MRP1 in relapsed diseases 53 .…”
Section: Mdr1 In Lung Tumorsmentioning
confidence: 88%
“…In the investigation by Trussardi-Regnier et al, expression of three major resistance genes MDR1, MRP1 and LRP was simultaneously investigated in small cell lung cancer, non-small cell lung cancer and metastasis 53 . Single biopsies of bronchoscopy from 73 patients were performed to investigate expression of these three resistance genes by reverse transcriptase-polymerase chain reaction.…”
Section: Mdr1 In Lung Tumorsmentioning
confidence: 99%